Ketaatan Masyarakat Internasional terhadap Hukum Internasional dalam Perspekti Filsafat Hukum - Author: Sefriani (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The research is aimed to figure out whether the International Law is a genuine law. This concerns with why the international community is willing to obey the international law though it lacks of formal institutions that are in charge of empowering the law. This is a normative legal research. The data used in this research are the secondary data along with the secondary law material that is in the form of research result. Through this research, it can be concluded that the nature of coordinative relationship among international community - not having a supranational institution that has an authority in making and forcing the validity of certain international regulation at once to the citizens of nations that are breaking the international law – will not decrease the existence and the essence of the international law as a legal norm. The most major factor emerging the acceptance and the obedience of the international community towards its regulation is the awareness and the needs of all people towards which regulation that can offer the law and order, justice, and law enforcement that can be done and of which can not be done in the practice of the international law. The internally emerged obedience will offer a better result that the one emerged by the punishment.